Feasibility Study of the Utilization of Water in the Seruyan River Watershed in Kuala Pembuang, Seruyan Regency, Central Kalimantan - Rika Fitriani; Ukik Agustina (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
River water is one of the main sources of community needs in rural areas, including in Seruyan Regency. This study aims to assess the feasibility of utilizing water from the Seruyan River Basin (DAS) for public health. The research method uses a qualitative approach with data triangulation and water pollution index analysis based on environmental quality standards. Data were obtained from field observations, documentation studies, and in-depth interviews with residents, community health center officers, village officials, and environmental agencies. The results show that the water pollution index of the Seruyan River Basin is in the light to moderate pollution category, with water quality not yet fully meeting quality standards for household clean water needs. Residents still use river water for bathing, washing, and daily activities, despite frequent complaints of skin problems and digestive disorders. Interviews with health workers confirmed that skin disease complaints are quite high in the riverbank area. It was concluded that the use of Seruyan River water is unsuitable for direct consumption without treatment. Improvements in water quality management, public education, and local government policies regarding clean water provision are recommended.